Förekomst av Giardia i symtomfria valpkullar - Florén, Andreas (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2008)
The flagellate Giardia intestinalis has been known to cause diarrhea in both man and dog. Results from epidemiological studies have indicated that transmission of the parasite from dog to man is plausible even though that route of infection has yet to be shown. Several international studies have shown that the parasite frequently occurs in asymptomatic dogs. In Sweden the prevalence of Giardia in healthy dogs is not known though. In this study, faecal samples were collected at two separate occasions from 21 litters and 21 bitches showing no symptoms from the gastrointestinal tract. The samples from each litter were pooled but the samples from the bitches were analyzed individually. All of the samples were analyzed both by immunofluorescence (Waterborne Cyst-a-Glo Kit) and an ELISA test (ProSpect Giardia Microplate Assay).